Enhancing Augmented Reality (AR) Technology to Improve Medical English Literacy - Hashim, Haida Umiera; Saragih, Erikson; Mahriyuni; Gapur, Abdul (TALENTA, 2024)
Since the paradigm for teaching reading has shifted from traditional literacy to multimodal literacy, prior research has demonstrated that augmented reality (AR) technology can successfully improve conventional literacy in general language learning. Only a few research, particularly in English for Nurse courses, have examined the potential of Augmented Reality (AR) technology to improve multimodal literacy in ESP learning. The purpose of this study was to determine how AR technology affects nursing students' multimodal literacy in ESP learning and how they communicate with others through a variety of multimodal modalities to improve their multimodal literacy in medical English. Fifty nursing students enrolled in English for Nursing courses participated in the study to share their experiences using this multimodal ESP learning survey to improve their medical English literacy. In the auditory mode, background music and sound effects were used to elicit strong emotions and improve immersive experiences. The results also showed a significant improvement in nursing students' multimodal English literacy skills when the material was created for a location-based augmented reality application. The findings revealed that nursing students used three modes in AR (visual, imaging, and animations). The three modes were used to help viewers comprehend complex material, give them specific ideas, and encourage participation.